Sosialisasi Tentang Mengenalkan Pengelolaan Keuangan pada Anak Usia Dini di Panti Asuhan Dompet Yatim dan Dhuafa Jati Asih Bekasi - Ifah Masrifah; Dewi Tri Mulyaningsih; Anugerah Putri Widyastuti; Arika Dania; Ari Saptono; Bibah Haerani; Putri Rahmadani; Siva Izah; Vicky Paradise Albina (Jurnal Informasi Pengabdian Masyarakat, 2025)
Important Educational Activities for financial management in the form of saving from an Early Age aim to explain and offer an understanding of achieving goals while educating participants about the meaning of saving as financial management for Islamic boarding school children and the value of introducing money. From an early age, it is important to assess the knowledge, understanding, and thought processes of Islamic boarding school children about the importance of saving and living frugally. Thus, they want to better understand and equip themselves to be more disciplined in managing and controlling their money and using their resources wisely for various needs in the future.